2023
DOI: 10.1021/acsami.3c00369
|View full text |Cite
|
Sign up to set email alerts
|

BiOBr Surface-Functionalized Halide Double-Perovskite Films for Slow Ion Migration and Improved Stability

Abstract: Surface-tailored lead-free halide double-perovskite (Cs2AgBiX6) thin films are utilized for ion migration studies. A thin surface layer of BiOBr/Cl is grown via intentional annealing of the halide films in ambient conditions. Herein, we physically stacked the two films, viz., Cs2AgBiBr6 and Cs2AgBiCl6, to thermally activate the halide ion migration at different temperatures (room temperature (RT)–150 °C). While annealing, the films’ color changes from orange to pale yellow and transparent brown to yellow as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…51 The thermally activated anion diffusion between physically paired MAPbBr 3 and MAPbI 3 films have been explored by Elmelund et al 52 Similarly, Bhawna et al studied the halide ion diffusion kinetics across stacked Cs 2 AgBiCl 6 and Cs 2 AgBiBr 6 thin films at different temperatures. 53 Taking advantage of interfacial anion mixing, Bian et al have synthesized a component-graded heterojunction between CsPbBrI 2 /CsPbI 3 that exhibits suitable band bending and improves charge carrier transport. 54 In contrast, for developing stable heterostructures in novel all-perovskite architecture, the interfacial anion migration must be mitigated.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 The thermally activated anion diffusion between physically paired MAPbBr 3 and MAPbI 3 films have been explored by Elmelund et al 52 Similarly, Bhawna et al studied the halide ion diffusion kinetics across stacked Cs 2 AgBiCl 6 and Cs 2 AgBiBr 6 thin films at different temperatures. 53 Taking advantage of interfacial anion mixing, Bian et al have synthesized a component-graded heterojunction between CsPbBrI 2 /CsPbI 3 that exhibits suitable band bending and improves charge carrier transport. 54 In contrast, for developing stable heterostructures in novel all-perovskite architecture, the interfacial anion migration must be mitigated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Lai et al fabricated CsPbCl 3 –CsPbBr 3 single-crystalline perovskite nanowire with a heterojunction and then studied the defect-mediated anion intermixing using confocal and wide-field photoluminescence measurements . The thermally activated anion diffusion between physically paired MAPbBr 3 and MAPbI 3 films have been explored by Elmelund et al Similarly, Bhawna et al studied the halide ion diffusion kinetics across stacked Cs 2 AgBiCl 6 and Cs 2 AgBiBr 6 thin films at different temperatures . Taking advantage of interfacial anion mixing, Bian et al have synthesized a component-graded heterojunction between CsPbBrI 2 /CsPbI 3 that exhibits suitable band bending and improves charge carrier transport …”
Section: Introductionmentioning
confidence: 99%
“…Notably, Cs 2 AgBiBr 6 has demonstrated remarkable photodetection properties [26][27][28]. Cs 2 AgBiCl 6 has a shown a significant response to x-ray radiation [29], while previous research has predominantly focused on the Cs 2 AgBiCl 6 or Cs 2 AgBiCl 6 films [30][31][32]. Despite the advances mentioned above, the instability due to oxygen, temperature and moisture, etc is the main issue for perovskite-based devices and research on it is scarcely reported.…”
Section: Introductionmentioning
confidence: 99%